2021
DOI: 10.23922/jarc.2020-046
|View full text |Cite
|
Sign up to set email alerts
|

Bridge to Surgery for Obstructing Colonic Cancer: A Comparison between Right- and Left-sided Lesions

Abstract: Objectives: Few studies have compared management and outcomes of bridge to surgery (BTS) for obstructive colonic cancer according to the location of the tumor. Additional information is needed about this procedure's characteristics and short-term and long-term outcomes. We aimed to compare patient and tumor characteristics, and outcomes of BTS for obstructive right-sided versus left-sided colonic cancers. Methods: This was a retrospective, single center, cohort study. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Some studies have reported that right-sided OCC has a worse prognosis than left-sided OCC ( 10 12 ). However, other studies have shown no differences in oncologic outcome between left-side and right-side OCCs ( 13 , 14 ). Accordingly, the aim of this study was to compare oncologic outcomes of IOCC patients with those of non-obstructive colon cancer (NOCC) patients.…”
Section: Introductionmentioning
confidence: 79%
“…Some studies have reported that right-sided OCC has a worse prognosis than left-sided OCC ( 10 12 ). However, other studies have shown no differences in oncologic outcome between left-side and right-side OCCs ( 13 , 14 ). Accordingly, the aim of this study was to compare oncologic outcomes of IOCC patients with those of non-obstructive colon cancer (NOCC) patients.…”
Section: Introductionmentioning
confidence: 79%
“…However, to the best of our knowledge, no study has directly compared postoperative outcomes. Even though a recent study by Sugiura et al compared the postoperative outcomes of BTS according to the tumor site and reported that right-sided cancers had higher rates of postoperative complications, decompression procedures for BTS included stoma and transnasal ileus tube [25].…”
Section: Discussionmentioning
confidence: 99%